Biodiversity of Antimicrobial-Producing Actinomycetes Strains Isolated from Dry Dipterocarp Forest Soil in Northeast Thailand - Chanthasena,Panjamaphon (2016)
The increasing use of antibiotics has led to the development of drug-resistant microorganisms. The emergence of resistant strains has compromised the treatment and control of infectious diseases. As a result, the search and development of a novel class of antibiotic drugs are required. Actinomycetes have been recognized as a richest source of secondary metabolites including antibiotics. The aim of this study was to investigate the diversity of antibiotic-producing soil Actinomycetes from dry dipterocarp forest in Northeast of Thailand. The soil from this area has been known for its poor in nutrients and highly acidic with pH values around 4.5. In such a harsh condition, soil-inhabiting Actinomycetes elevate their protective mechanisms by inducing the production of antimicrobials and other defense compounds. Therefore, dry dipterocarp forest could be served as a potential source for the screening of the novel antimicrobial drugs. Twelve antibiotic-producing strains isolated from soil in Suranaree University of Technology produce antimicrobial agents which are active against wide range of test pathogens including methicillin-resistant Staphylococcus aureus (MRSA). Based on 16S rRNA gene analysis, these strains are close affiliated with the genus Streptomyces (11 isolates) and Nonomuraea (1 isolate). Most of soil isolates show narrow antimicrobial spectrum activity against Gram-positive bacteria. Two isolates, PJ36 and PJ95, exhibit broad antimicrobial spectrum against Gram-positive bacteria, Gram-negative bacteria and yeasts. Phylogenetic tree analysis of 16S rDNA reveals that isolates PJ33, PJ36, PJ43, PJ51, PJ75, PJ76, PJ77, PJ85, PJ88 and PJ95 strains are not cluster with others strain of Streptomyces. They represent a distinct phyletic line which might be suggested the novel strains. This study was the first attempted to isolate antibiotic-producing Actinomycetes from dry dipterocarp forest soil in Northeast Thailand. Most of soil isolates (8 strains) obtained from this study were active against methicillin-resistant Staphylococcus aureus (MRSA). These isolates could be used for the development of new drugs to combat antibiotic resistances.